Illustrate the Butterfly Effect on the Chaos Rikitake system - Yousof Gholipour; Amin Ramezani; Mahmood Mola (Bulletin of Electrical Engineering and Informatics, 2014)
This letter presents butterfly effect on a Chaos system. In this letter we want to briefly introduce Chaos Rikitake system and monitor the butterfly effect on this system. In chaos theory, the butterfly effect is the sensitive dependency on initial conditions. For this goal at the first we suppose initiation point and plot it, for base of work, later will apply small change on one item of initiation point and monitor behavior of Rikitake system. At the end we want to reclaim the famous lecture of Edward Lorenz in 1972 “Does the flap of a butterfly’s wings in Brazil set off a tornado in Texas?”. The numerical simulations by use of MATLAB software are given to illustrate the butterfly effect on this system.